PENGARUH KEPEMIMPINAN ISLAMI, MOTIVASI KERJA ISLAMI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA ISLAMI DAN KINERJA KARYAWAN BAITUL MAAL WA TAMWIL (BMT) - Moh. Musfiq Arifqi (Program Studi Perbankan Syariah, 2020)
The main purpose of this research is to explore employee???s performance at BMT NU Jawa Timur. It is measured from the internal institution, through Islamic leadership, Islamic work motivation, organizational culture, and Islamic job satisfaction. This research used a quantitative approach based on the results of questionnaires and documentation. Data was processed by using path analysis with IBM SPSS Amos software, 21.0. The results of this research indicate that all hypotheses are received. It was showed that Islamic leadership positively and significantly effects on organizational culture. Islamic leadership positively and significantly effects on Islamic work motivation. Islamic leadership positively and significantly effects on Islamic job satisfaction. Islamic work motivation positively and significantly effects on organizational culture. Islamic work motivation positively and significantly effects on Islamic job satisfaction. Organizational culture negatively and significantly effects on Islamic job satisfaction. Organizational culture positively and significantly effects on employee???s performance. Islamic job satisfaction positively and significantly effects on employee???s performance.